Reflections on the TRC’s Mandate to Law Schools: Microscopic and Macroscopic Changes - Lavallee, Jaime M.N.; Hansen, Robin F. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2024)
The Truth and Reconciliation Commission’s [TRC] mandate to law schools is multi-faceted in its pedagogical substance and process. The mandate entails rejecting terra nullius and its associated colonial assumptions within Canadian law as taught and a new valorization of Indigenous legal orders. This change is challenging because it can implicate law school community members’ sense of individual personal and professional identities. Understanding the depth of these potential implications can help to explain TRC implementation as a long-term project, involving growth at both individual and institutional levels. To fulfill the TRC mandate, one law school changed the requirements for a law degree, including adding a class into the first year program. This addition was reviewed internally in 2023. The internal review identified several challenges; in particular, the course attempted to cover too many diverse topics and objectives within a single class. The course was also placing significant demands on instructors (and students) due to occurrences of interpersonal conflict and racism, as well as students’ disparate levels of background knowledge. Curriculum proposals were made that aimed to manage learner defensiveness, reduce instances of racism in communications, and decouple distinct topics and learner objectives from one another, allowing for more effective instruction, scheduling, and learning. By using a settler harm reduction approach to legal education, as well as the goals of decolonization and Indigenization, we explain the challenges identified in the internal review and responses proposed. We discuss change as a multilevel process and consider how individuals’ experiences can inform broader curriculum and institutional choices.